Don't think of them as roads. Think of them as road transport markets: Congestion pricing as a neoliberal political project. (October 2017) - Vanoutrive, Thomas
Highlights: Planners have promoted road pricing as a progressive measure. Congestion pricing is a neoliberal political project that originated in the 1950s. Understanding congestion pricing requires insight in the history and sociology of the idea. Criticisms of road pricing are based on technical, equity and normative arguments. Abstract: For some time now, many planners have embraced the idea of congestion pricing, an idea that has its origins in the field of transport economics. A positive attitude towards pricing, however, seems to be at odds with values commonly held by planners. To clarify this paradox, we need to thoroughly understand the history and sociology of the idea, and to acquire such understanding, this dialogue discusses the claim that the history of thinking about congestion pricing can best be understood by seeing it as a discursive politics of the market. The current view on congestion and road pricing originated in the 1950s, and there is clearly a link between the dissemination of the idea of congestion pricing and the rise of neoliberal thinking in general, although a different, rather Keynesian, tradition has continued to exist since the early days. The article also presents some criticisms of congestion pricing based on technical, equity as well as normative arguments. Finally, some attention is devoted to the format of the paper, given that it is written as a dialogue.